2015
DOI: 10.1177/0333102415583144
|View full text |Cite
|
Sign up to set email alerts
|

Reduced functional connectivity between salience and visual networks in migraine with aura

Abstract: The unique pattern of connectivity changes found in interictal MA patients involved area V3A, an area previously implicated in aura generation. Hypoconnectivity to this and other occipital regions may either represent a compensatory response to occipital dysfunctions or predispose MA patients to the development of aura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 48 publications
8
65
1
Order By: Relevance
“…The NTS is known to send monosynaptic projections to higher brain regions such as the parabrachial nucleus, ventromedial medulla, periaqueductal gray, anterior cingulate and lateral prefrontal cortex [8; 64] - regions hypothesized to support VNS therapeutic effects [81]. Altered connectivity in these pain-processing regions has been noted in interictal migraine patients [25; 29; 55; 67; 79]. Abnormalities in insula connectivity are of particular relevance, given that this region integrates multimodal afference from somatosensory, nociceptive and visceral streams with activity in prefrontal cortex, limbic structures, and olfactory, visual and auditory processing regions [11].…”
Section: Discussionmentioning
confidence: 99%
“…The NTS is known to send monosynaptic projections to higher brain regions such as the parabrachial nucleus, ventromedial medulla, periaqueductal gray, anterior cingulate and lateral prefrontal cortex [8; 64] - regions hypothesized to support VNS therapeutic effects [81]. Altered connectivity in these pain-processing regions has been noted in interictal migraine patients [25; 29; 55; 67; 79]. Abnormalities in insula connectivity are of particular relevance, given that this region integrates multimodal afference from somatosensory, nociceptive and visceral streams with activity in prefrontal cortex, limbic structures, and olfactory, visual and auditory processing regions [11].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a number of recent rs-fc MRI studies have indicated abnormal fc within the salience network, a core resting-state network that includes paralimbic-limbic regions believed to play a role in the detection of stimuli and the allocation of attentional resources. Rs-fc results indicate heightened connectivity within the salience network in migraineurs without aura [68] and reduced functional connectivity between the salience and the visual networks in migraine patients with aura [69].…”
Section: Attention/cognition Deficits In Migraine: An Ongoing Debatementioning
confidence: 92%
“…We can expect that the reporting of premonitory symptomatology is going to be different in the paediatric population, depending on age and cognition, and because of dependence on a third party history and assessment for the symptoms through a parent, teacher or carer. Additionally, features such as face changes may be caused by pallor or facial swelling, flushing or sweating, which we would interpret as cranial autonomic features [30••]. There is of course the possibility that face changes could be related to irritability and low mood.…”
Section: Introductionmentioning
confidence: 99%
“…These have included cranial allodynia, cranial autonomic symptoms such as nasal stuffiness and flushing, as well as facial pallor to name a few [30••]. Additionally, data analysis from retrospective studies does not allow true estimation of the population prevalence of premonitory symptoms as the study data collection populations from all the studies are so varied, and apart from the Giffin and Quintela studies, the studies do not look at the reproducibility of these symptoms across serial attacks [14, 15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation